Curating popular music: authority and history, aesthetics and technology. Issue 3 (28th August 2014) - Atton, Chris
Abstract: The practice of curation in popular music may be seen as a form of historical enquiry that works in a similar way to the critical projects of the 'new museology'. Self-curation can be employed by musicians to re-present their work as a historiographical project of popular music and as an intervention in dominant critical accounts of the musicians' creative practices. The challenge to conventional historiography can be understood as a project of archaeology in the Foucauldian sense, where discourses surrounding objects and their histories may be contested and reinvigorated through a process of recollecting/re-collecting that also recalls Walter Benjamin's challenge to historicism. Using the work of Robert Fripp and King Crimson as an example of musician-curated recordings, I argue that legal and economic control may become a basis for aesthetic control, through which histories of creativity may be rewritten. The act of recollection/re-collection becomes a route through which musicians are able to engage with critical contexts and genre formations, and to contribute actively to the material culture of their own history.